2019
DOI: 10.1038/s41386-019-0485-6
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread white matter microstructural abnormalities in bipolar disorder: evidence from mega- and meta-analyses across 3033 individuals

Abstract: Fronto-limbic white matter (WM) abnormalities are assumed to lie at the heart of the pathophysiology of bipolar disorder (BD); however, diffusion tensor imaging (DTI) studies have reported heterogeneous results and it is not clear how the clinical heterogeneity is related to the observed differences. This study aimed to identify WM abnormalities that differentiate patients with BD from healthy controls (HC) in the largest DTI dataset of patients with BD to date, collected via the ENIGMA network. We gathered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
122
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 44 publications
21
122
5
1
Order By: Relevance
“…The authors found white matter microstructure alterations principally within the cingulum, the main pathway in the limbic system, and in interhemispheric connectivity by the corpus callosum. 247 Thus, DTI studies have shown consistent abnormalities in regions associated with emotional regulation as well as in structures that integrate these regions interhemispherically.…”
Section: Neuroimaging Findings In Bipolar Disordermentioning
confidence: 93%
See 1 more Smart Citation
“…The authors found white matter microstructure alterations principally within the cingulum, the main pathway in the limbic system, and in interhemispheric connectivity by the corpus callosum. 247 Thus, DTI studies have shown consistent abnormalities in regions associated with emotional regulation as well as in structures that integrate these regions interhemispherically.…”
Section: Neuroimaging Findings In Bipolar Disordermentioning
confidence: 93%
“…The results showed that offspring of parents with BD had lower functional connectivity between the right ventral striatumleft caudal anterior cingulate in response to loss; and higher functional connectivity between the right pars orbitalis-left and right orbitofrontal cortex in response to reward, indicating potential neural markers for the risk of BD. 255 Despite the impressive advances in technology and interesting neuroimaging findings associated with a psychiatric diagnosis, 247 as well as the response to treatment and risk identification, 255,256 there is still no direct clinical application of brain imaging at this moment in psychiatry.…”
Section: Neuroimaging Findings In Bipolar Disordermentioning
confidence: 99%
“…Future multisite brain-imaging machine learning studies will begin to move towards sharing of more detailed individual subject data, not only a selection of discrete features or site-level results derived from a single modality; unsupervised machine learning techniques may offer potential to better understand the heterogeneity in the disorder. The ENIGMA-BD DTI WG conducted both a mega-and meta-analysis of 3033 subjects (1482 BD and 1551 controls) 69 . Both analyses found lower FA in patients with BD compared with healthy controls in most brain regions, with the highest effect sizes in the corpus callosum and cingulum.…”
Section: Enigma-bdmentioning
confidence: 99%
“…Zhang-James 94 ; Hess et al 92 Reduction in bilateral amygdala, striatal, and 97 ; van Rooij et al 8 Altered morphometry in the cognitive and affective parts of the striatum, frontal cortex and temporal cortex in ASD. BD 44 11,100 (3100) 8- 86 Favre et al 69 ; Nunes et al 23 ;…”
Section: Introductionmentioning
confidence: 99%
“…Here, we applied this approach to investigate the microstructural organization of white matter in PTSD. The ENIGMA DTI workflow 38 , which has successfully identified white matter compromise in schizophrenia 39 , bipolar disorder 40 , major depression 41 , and 22q11.2 deletion syndrome 42 , among others, was used by 28 cohorts to process their DTI data locally. We hypothesized the largest effects of compromised microstructure will be evident in the fronto-limbic tracts, such as the cingulum, uncinate, fornix, and corpus callosum; these tracts are strongly implicated in behavioral deficits of PTSD such as emotion regulation, working memory, and episodic memory 10,16,19,20,24,43 .…”
Section: Introductionmentioning
confidence: 99%